2022
DOI: 10.1007/s15010-022-01852-5
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in cancer patients with SARS-CoV-2 or seasonal influenza: an observational cohort study from a German-wide hospital network

Abstract: Purpose At the beginning of the COVID-19 pandemic, SARS-CoV-2 was often compared to seasonal influenza. We aimed to compare the outcome of hospitalized patients with cancer infected by SARS-CoV-2 or seasonal influenza including intensive care unit admission, mechanical ventilation and in-hospital mortality. Methods We analyzed claims data of patients with a lab-confirmed SARS-CoV-2 or seasonal influenza infection admitted to one of 85 hospitals of a German… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In line with our results, Cangemi et al found in a prospective cohort study that COVID-19 was associated with a five-fold increase in the in-hospital mortality rate compared to NC-CAP [6]. In a retrospective analysis of hospitalized patients with COVID-19 or Influenza A from a nation-wide hospital network in Germany, Kodde et al found that COVID-19 was associated with three-fold increased odds for in-hospital death than Influenza A patients [27]. Serrano Fernandez et al observed rates of in-hospital death and invasive MV twice as high in COVID-19 pneumonia than in bacteremic pneumococcal CAP [28].…”
Section: Discussionsupporting
confidence: 85%
“…In line with our results, Cangemi et al found in a prospective cohort study that COVID-19 was associated with a five-fold increase in the in-hospital mortality rate compared to NC-CAP [6]. In a retrospective analysis of hospitalized patients with COVID-19 or Influenza A from a nation-wide hospital network in Germany, Kodde et al found that COVID-19 was associated with three-fold increased odds for in-hospital death than Influenza A patients [27]. Serrano Fernandez et al observed rates of in-hospital death and invasive MV twice as high in COVID-19 pneumonia than in bacteremic pneumococcal CAP [28].…”
Section: Discussionsupporting
confidence: 85%
“…Notably, fatality rates ranging from 5% to 33% have been reported for cancer and hemopoietic stem cell transplant (HSCT) recipients with influenza [31,[34][35][36]. Furthermore, influenza infection often delays the initiation of anticancer treatment or interrupts ongoing treatment, worsening the oncologic outcome [6].…”
Section: Rationale and Evidencementioning
confidence: 99%
“…While both influenza A and SARS‐CoV‐2 viral infections during anti‐cancer therapy have been linked to increased mortality, elevated hospitalization rates and treatment delays, 2,3 the potential for utilizing viruses as therapeutic agents is also being explored. The study by You et al provides the first clinical evidence of the anti‐tumour effect of Influenza A virus in a refractory AML patient, thereby furnishing unique insights into the potential therapeutic benefits of Influenza A virus infection for haematological malignancies.…”
Section: Figurementioning
confidence: 99%